From Green Growth to the Blue Growth in the 2030 Agenda Goals - F. de Carvalho Figueiredo; C.M. Salca Rotaru (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
Economic growth is linked to the development and use of natural resources. With the emergence of the idea of sustainable development, the idea of green economy or bioeconomy is born, based on better management of natural resources, through the use of environmentally friendly economic instruments. The new objectives of sustainable development are related to both water protection and responsible consumption and production. This makes the transition from the green economy to the blue bioeconomy. This article examines the link between the blue bioeconomy and the goals of sustainable development in the light of new environmental policies and regulations. The conclusions are that the blue bioeconomy, complementing the green economy, can ensure the decoupling of economic development from the intensive use of non-renewable resources and that together they can lead to a better achievement of sustainable development goals.